Improved Survival and Retinal Function of Aging ZDF Rats in Long-Term, Uncontrolled Diabetes by BGP-15 Treatment - Wachal, Zita; Szilágyi, Anna; Takács, Barbara; Szabó, Adrienn Mónika; Priksz, Dániel; Bombicz, Mariann; Szilvássy, Judit; Juhász, Béla; Szilvássy, Zoltán; Varga, Balázs (Frontiers in Pharmacology, 2021)
Retinal complications of diabetes often lead to deterioration or even loss of vision. This hastens discovery of pharmacological agents able to counterbalance diabetic retinopathy. BGP-15, an emerging small molecule agent, was formerly proven by our workgroup to be retinoprotective on non-obese diabetic animals, Goto-Kakizaki rats. In the present study we aimed to examine its long-term tolerability or incidental side-effects on obese-prone Zucker Diabetic Fatty (ZDF) rats to further increase the rationale for a future humantranslation. To make terminal visual status comparable with our other investigations, we also carried out electroretinography (ERG) at the end of the experiment. Our study was started on 16-week-old ZDF rats and lasted for 52 weeks, while BGP was administered daily by gavage. During the 12 months of treatment 100% of BGP-treated animals survived compared to the non-treated ZDF group, where 60% of the animals died, which was a statistically significant difference. Based on ERG results BGP-15 was able to counterbalance visual deterioration of ZDF rats caused by long-term diabetes. Some moderate but significant changes were seen in OGTT results, and some relationship to oxidative stress by western blot method: BGP-15 was able to increase expression of HSP70 and decrease that of NFkB in eyes of rats. These were in concert with our previous observations of SIRT1-increment and MMP9-decrement in diabetic eyes by BGP. In summary, not only is BGP-15 not harmful in the long run, but it is even able to reduce the related mortality and the serious consequences of diabetes. BGP-15 is an excellent candidate for future drug-development against diabetic retinopathy.